2009
DOI: 10.1007/s00296-009-0900-0
|View full text |Cite
|
Sign up to set email alerts
|

Higher genetic susceptibility to inflammation in mild disease activity of systemic lupus erythematosus

Abstract: In order to test the hypothesis that stratification of Mexican Modification of the Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI) simplifies the genetic study of SLE, we evaluated the genetic susceptibility to inflammation and defects in clearance of immune complexes among SLE patients in Taiwan. SLE phenotypes were stratified according to the MEX-SLEDAI scores into two subgroups (10), and then according to renal disorder and neurological disorder, aiming to minimize any loss of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Polymorphisms in the IL1 gene have been associated with other autoimmune diseases such as rheumatoid arthritis [49], inflammatory bowel disease [50], and systemic lupus erythematosus [51]. IL1β has pleiotropic effects, can alter cytokine production, cell signaling and migration, [52].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the IL1 gene have been associated with other autoimmune diseases such as rheumatoid arthritis [49], inflammatory bowel disease [50], and systemic lupus erythematosus [51]. IL1β has pleiotropic effects, can alter cytokine production, cell signaling and migration, [52].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of IL1α and IL1β polymorphisms in SLE have been contradictory (Camargo et al, 2004;Huang et al, 2002;Kobayashi et al, 2007;Muraki et al, 2004;Parks et al, 2004;Sánchez et al, 2006;Tsai et al, 2009). The discordant results among genetic investigations of complex diseases may account for clinical heterogeneity, ethnic differences, real genetic heterogeneity, and small sample sizes (Lee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-nine studies were identified after electronic searches, and 8 case-control studies in 7 articles (one article containing data on two different populations; Parks et al, 2004) addressed IL1α and IL1β polymorphisms with SLE and met the inclusion criteria (Table 1) (Camargo et al, 2004;Huang et al, 2002;Kobayashi et al, 2007;Muraki et al, 2004;Parks et al, 2004;Sánchez et al, 2006;Tsai et al, 2009). For the IL1β − 511C/T polymorphism, six studies comprised three Asian, one African-American, one White-American and one Colombian population samples.…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…Many studies have found out that there is a significant genetic susceptibility in SLE onset [21]. In the early 90s, the polymorphism site of TNF-gene Nco at the HLA class area was discovered and TNF * 1 allele frequency in SLE patients in German -derived population was significantly higher than that in the control group [28].…”
Section: Discussionmentioning
confidence: 99%
“…Production of TNF is altered in SLE patients and correlated with disease activity [9][10][11].Experimental models of SLE show an abnormal TNF activity [12][13][14], which can be manipulated to change patterns of the disease onset or the severity [15,16]. In some models, genetic variation in TNF has been shown to be associated with differences in susceptibility [17][18][19][20][21]. LT-is a new member of TNF family, its gene is located in MHC class areas which are closely linked with TNF -, TNF -gene, and it was consider that it was closely related to the immune regulation since it was discovered [22].…”
Section: Introductionmentioning
confidence: 99%